CONTRASTIVE ANALYSIS OF SOME TOURISTIC TERMS IN ENGLISH AND UZBEK LANGUAGES - Umarova Zebo Xafizovna (Scholar Express Journal, 2024)
In the lexical – semantic analysis of the terminology of tourism, it should be noted that on the one hand , on the lexical level there is a more mature status of English terminology in the field of Tourism and appears as a basis in the Uzbek language . On the other hand, in recent times there is a tendency to parallelism in the lexical- semantic processes of English and Uzbek languages. Thus, it can be said that the terminology of tourism is distinguished by the internationality of its components, which, first of all , depends on the processes of globalization, which led to the convergence of concretionary and terminological systems, that is, the emergence of a common part of the terminological vocabulary for both languages
Keywords: Tourism; Term; Terminology; Vocabulary